Was once a hero [videorecording (DVD)] - Searles, Dan; Smith, Paige; Hinton, Darby; Kashmanian, Julie; Cash, John Carter; Holden, Rebecca (BMG Global, 2025)
After their father is brutally murdered by an outlaw, Ginny and her brother flee through a treacherous desert. They team up with a memory-impaired ex-war hero as they race toward the elusive sanctuary of Black Ridge. Will they survive?